The Evolution of E-Government in Saudi Arabia: A Comprehensive Review of Digital Transformation Strategies, Institutional Readiness, and Citizen-Centric Service Delivery in The Vision 2030 Era - Abn_hammad , Mohammed Zaid M.; Mohamed, Ibrahim Bin; Yahaya, Jamaiah Binti (International Journal of Accounting and Economics Studies, 2025)
This literature review provides a comprehensive examination of the evolution of e-government in Saudi Arabia during the Vision 2030 era, focusing on digital transformation strategies, institutional readiness, and citizen-centric service delivery. A systematic review methodology synthesizes findings from scholarly studies and government reports, tracing progress from early e-government initiatives to recent digital transformation programs. The analysis reveals significant strides in implementing e-government aligned with Vision 2030, including the digitization of over 97% of public services and the establishment of institutional frameworks like the Digital Government Authority (DGA) and the Saudi Data & AI Authority (SDAIA). Key findings highlight leadership commitment and cross-agency collaboration as drivers of improved service integration, reflected in Saudi Arabia’s rise to the top 20 in global e-government rankings by 2024 (Mitchell, 2022). The shift towards citizen-centric platforms has enhanced accessibility and user satisfaction. The review also examines economic benefits, such as cost savings and job creation, aligning e-government with fiscal governance. However, challenges such as digital literacy gaps, cybersecurity risks, and interoperability issues persist, with limited studies exploring user resistance or socio-cultural impacts. This review consolidates knowledge on Saudi Arabia’s digital transformation, identifies critical success factors and barriers, and proposes research gaps, such as longitudinal studies on user trust, to inform future strategies.